Phospholipase D1 downregulation by α-synuclein: Implications for neurodegeneration in Parkinson's disease - Conde, Melisa Ailén (2018)
We have previously shown that phospholipase D (PLD) pathways have a role in neuronal degeneration; in particular, we found that PLD activation is associated with synaptic injury induced by oxidative stress. In the present study, we investigated the effect of α-synuclein (α-syn) overexpression on PLD signaling. Wild Type (WT) α-syn was found to trigger the inhibition of PLD1 expression as well as a decrease in ERK1/2 phosphorylation and expression levels. Moreover, ERK1/2 subcellular localization was shown to be modulated by WT α-syn in a PLD1-dependent manner. Indeed, PLD1 inhibition was found to alter the neurofilament network and F-actin distribution regardless of the presence of WT α-syn. In line with this, neuroblastoma cells expressing WT α-syn exhibited a degenerative-like phenotype characterized by a marked reduction in neurofilament light subunit (NFL) expression and the rearrangement of the F-actin organization, compared with either the untransfected or the empty vector-transfected cells. The gain of function of PLD1 through the overexpression of its active form had the effect of restoring NFL expression in WT α-syn neurons. Taken together, our findings reveal an unforeseen role for α-syn in PLD regulation: PLD1 downregulation may constitute an early mechanism in the initial stages of WT α-syn-triggered neurodegeneration.